Membangun Personal Branding pada Siswa – Siswi SMK Wiyata Satya Jakarta Barat (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The use of social media is no longer just for information and entertainment, but has developed into a strategic means in building a positive self-image in the eyes of the public. School students are generally active users of social media whose intensity of use is quite high in daily life. As a group of teenagers who are still in the phase of finding their identity and tend to be emotionally labile, they need the right education to be able to use social media wisely, productively, and responsibly. Community Service activities carried out for students of SMK Wiyata Satya are expected to increase understanding of the importance of personal branding from an early age. Through this activity, students are not only given socialization about the concept of personal branding and social media ethics, but also equipped with practical skills in compiling portfolios and fostering awareness of career planning and goal achievement. At the end of the activity, students presented their self-concept that had been prepared and responded through a questionnaire to evaluate the effectiveness of the entire series of activities.